2018
DOI: 10.1016/j.jenvman.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simulated mechanical recycling processes on the structure and properties of poly(lactic acid)

Abstract: The aim of this work is to study the effects of different simulated mechanical recycling processes on the structure and properties of PLA. A commercial grade of PLA was melt compounded and compression molded, then subjected to two different recycling processes. The first recycling process consisted of an accelerated ageing and a second melt processing step, while the other recycling process included an accelerated ageing, a demanding washing process and a second melt processing step. The intrinsic viscosity me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
86
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 28 publications
19
86
0
1
Order By: Relevance
“…In opposite, significant decrease in the viscosity observed in the case of washed PLA wastes, results from influence of high temperature and shear stress during the polymer reprocessing. The degradation during the accelerated ageing can also contribute to this process (Beltrán et al 2018) An addition of oxidative stabilizers (quinone) and residual catalyst stabilizers (tropolone) to a neat polymer significantly limits the rheological degradation. The data obtained clearly identified that recycling reduces the mechanical strength of PLA.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In opposite, significant decrease in the viscosity observed in the case of washed PLA wastes, results from influence of high temperature and shear stress during the polymer reprocessing. The degradation during the accelerated ageing can also contribute to this process (Beltrán et al 2018) An addition of oxidative stabilizers (quinone) and residual catalyst stabilizers (tropolone) to a neat polymer significantly limits the rheological degradation. The data obtained clearly identified that recycling reduces the mechanical strength of PLA.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Determining the impact of recycling on the properties of polymers used for 3D printing is an important issue. It turns out that recycling with a washing stage results in a 20% decrease in PLA molecular weight (Beltrán et al 2018).…”
Section: Degradation Of Polymersmentioning
confidence: 99%
“…The reduction in molecular mass and introduction of new groups during degradation could further change the crystalline structure and might give rise to deteriorated mechanical properties of PLA. However, discrepant results have been reported 10‐12 . For instance, Pillin et al 12 reported that PLA displays declined fracture strength and strain‐at‐break after seven injection molding cycles.…”
Section: Introductionmentioning
confidence: 98%
“…However, PCL and EVOH are fossil fuel-derived plastics that increase carbon dioxide in the environment and stimulate the greenhouse effect. A thermo plastic polymer from a renewable source would be better for the development of a biodegradable plastic [5][6][7][8]. Poly Lactic Acid (PLA) is polyester made from L-or D -lactic acid.…”
Section: Introductionmentioning
confidence: 99%